Elaborasi Kemampuan Literasi Anak melalui Pendirian Rumah Baca Alam al Aly di Kedungglugu Gondang Nganjuk - Nur Rulifatur Rohmah; M. Yusuf; Syaiful Muda'i (Janaka, Jurnal Pengabdian Masyarakat, 2022)
This study discusses the elaboration of children's literacy skills, the target of assistance is taking cases to children in Kedungglugu village, Gondang district, Nganjuk district, this is considered important considering the low interest in reading and writing of children in the village. In simple terms, literacy is a basic ability that must be mastered by everyone, especially those at school age. This ability will serve as capital and provision in carrying out their daily lives in the future. However, the facts on the ground show that literacy skills, especially at the age of children, are quite alarming. Based on observations, one of the factors for the lack of interest in reading and writing in children is the absence of infrastructure that supports these literacy activities. Therefore, this mentoring initiated a concentration on the establishment of reading houses as a means for them to improve their literacy skills which will become the basis for their future life principles. The method used in this activity uses the Participatory Action Research (PAR) method with the main pillars of research, action, and participation. The partners involved in this program are all Muslim women and local village youth organizations.